Corrosion behavior of austenitic 304L and 316LN stainless steel clad reinforcing bars in cracked concrete. Issue 7 (12th January 2020) - Ogunsanya, Ibrahim G.; Strong, Victoria; Hansson, Carolyn M.
Abstract: A study has been conducted on the chloride‐induced corrosion behavior of 304L and 316LN stainless steel clad reinforcing bars (rebar) in concrete and in synthetic concrete pore solution. Metallographic examination of the as‐received clad bars confirmed a strong metallurgical bond at the core/clad interface and some grain growth interdiffusion of species at the interface. Both bars showed a wide variation in coating thickness around the rebar circumference, from a minimum of 0.32 and 0.60 mm to a maximum of 1.4 and 2.8 mm in the 304L clad and 316LN clad, respectively. The electrochemical results and visual examination after autopsy showed that active corrosion was yet initiated on either the solid and clad stainless steel or carbon steel rebar in the sound noncracked concrete specimens. In contrast, corrosion had initiated in the bars embedded in cracked concrete at the base of the crack and extended along or around the bars. In the concrete and synthetic pore solution tests, the current densities of both solid and clad stainless steel rebar exposed to ∼21% chloride brine solution for days between 400 and 1, 500 were similar. This was also the case for current densities of the straight and bent stainless steel bars tested in the synthetic pore solution test. Abstract : In the effort to find economical corrosion‐resistant reinforcing bars (rebar), clad stainless steel provides a suitable alternative. This article reports an evaluation of the metallurgical and long‐term corrosion properties of austenitic clad stainless steel rebar. These bars were tested in concrete conditions typical of bridge decks and exposed to an aggressive chloride environment in Ontario, Canada.